IMPLEMENTATION OF FELDSPAR AS PARTIALLY REPLACEMENT MATERIAL IN CEMENT MORTAR (EXPLORATION AND APPLICATION) - Edris, Walid Fouad; Al-Tamimi , Mahmoud; Aldelgawy, Mohammed (Journal of Applied Engineering Science, 2021)
This paper aims to explore and evaluate the use of Jordanian Feldspar as a natural resource partially replacement material for each of cement and sand in cement mortar. First, Al-Jaishia area was explored through a global positioning system (GPS) navigation to gather site samples of Feldspar raw material. Afterward, cement and sand were partially replaced by Feldspar with substitution ratios of 5%, 10%, 15%, 20%, and 25% for each. The study included the effect of cement replacement on normal consistency and setting time for cement paste. The water content along with initial and final setting times increased via the increment of cement replacement ratio. Moreover, mechanical properties (compressive, flexural, and residual compressive strengths) of cement mortar due to both cement and sand replacement were evaluated. The compressive and flexural strengths after 3, 7, and 28 days of curing were examined for both cement and sand replacement. While, residual compressive strength for cement replacement after 28 days was measured at elevated temperatures of 400°C, 600°C, and 800°C. The compressive and flexural strengths decreased by increasing the Feldspar replacement ratio for both cement and sand at all specimen ages. Whereas, heat resistance properties were improved by cement/Feldspar replacement. The best result for residual compressive strength was obtained at 15% replacement ratio and 400°C temperature.
Keywords: Feldspar, cement mortar, compressive strength, normal consistency, setting time, Palestine grid